PERAN ANAK-ANAK DALAM IKLAN TELEVISI - Linda Mega Silviana (ARTic, 2018)
Television advertisements played by children get violations related to advertising rules called EPI (Etika Pariwara Indonesia), including Tri Indie + ads, Wall’s Selection ads, and Forvita margarine advertisements. The message contained in the advertisements studied emphasizes more on the description of the nature, character, and way of view of children about the life around their environment in carrying the message content of each advertised product. The depiction of the perspective of advertising is packaged in an advertising approach and style that contains elements of criticism and comedy reinforced from the Wimba Content that depicts the stereotypes of children based on the attributes used, depictions of the environment that are close and in accordance with the character of the child, and the narrative in the ad.